Pengaruh Penyuluhan Kesehatan Reproduksi terhadap Pengetahuan Remaja tentang Seksual Pra Nikah di MTs Nurul Iman Kota Jambi - Rafika Bilhuda; Rini Mustikasari Kurnia Pratama (Jurnal Akademika Baiturrahim Jambi, 2022)
Adolescence is a period of transition between childhood to adulthood at this time which is often a problem for adolescents, namely knowledge which is influenced by education level, age, environment, culture, socio-economics.The purpose of this study was to determine the effect of reproductive health knowledge on premarital sex before and after being given counseling.This research is a type of pre-experimental research with a one group pretest-posttest research design. The variables studied were the effect of reproductive health counseling on adolescent knowledge about premarital sex, population 115teenagers, the research sample is 90 teenagers The source of data in this study was primary data, data obtained through questionnaires. The analysis used Bivariate and Univariate analysis. The research obtained 90 respondents to this study experienced an increase in knowledge before being given counseling an average answer score of 11.5, after counseling the average answer score is 14.1 and the p-value is 0.000 <0.05 then there is a significant influence on adolescent knowledge before and after counseling.